Perioperative ARDS and lung injury: for anaesthesia and beyond. (4th March 2018) - Wise, Robert; Bishop, David; Joynt, Gavin; Rodseth, Reitze
Abstract : Postoperative pulmonary complications are common and may be associated with significant cost. Acute respiratory distress syndrome (ARDS), a life-threatening respiratory disease process characterised by hypoxaemia and reduced lung compliance, is one of the more serious pulmonary complications. The development of ARDS or the related entity of lung injury is associated with prolonged hospitalisation, ventilation, and time spent in intensive care, and profoundly increases the risk of mortality and significant morbidity. Patients with, or at risk of ARDS and lung injury, must be identified, optimised and managed with sound intraoperative principles (particularly ventilation and fluid management) – with the specific aim of limiting harm. This review will focus on the diagnosis, pathophysiology, prevention and management of ARDS and lung injury in the perioperative period.